Mental health crisis care for children and young people aged 5 to 25 years: the CAMH-Crisis evidence synthesis - Evans Nicola; Edwards Deborah; Carrier Judith; Elliott Mair; Gillen Elizabeth; Hannigan Ben; Lane Rhiannon; Williams Liz (NIHR Journals Library, 2023)
Background Mental health care for children and young people is a rising concern, with one in six children aged 5-19 years in England having a probable diagnosable mental disorder. Care for children and young people in crisis is known to be delivered by multiple agencies using a range of approaches. Objectives The review objectives of this study were to critically appraise, synthesise and present the best-available international evidence related to crisis services for children and young people aged 5-25 years, specifically looking at the organisation of crisis services across education, health, social care and the third sector, and the experiences and perceptions of young people, families and staff, to determine the effectiveness of current models and the goals of crisis intervention. Methods All relevant English-language international evidence specifically relating to the provision and receipt of crisis support for children and young people aged 5-25 years, from January 1995 to January 2021, was sought. Comprehensive searches were conducted across 17 databases and supplementary searching was undertaken to identify grey literature. Two team members appraised all the retrieved research reports (except grey literature) using critical appraisal checklists. A separate analysis was conducted for each objective. Confidence in research findings was assessed using the Grading of Recommendations Assessment, Development and Evaluation and the Confidence in the Evidence from Reviews of Qualitative research approaches. Findings One hundred and thirty-eight reports were used to inform this evidence synthesis, including 39 descriptive accounts of the organisation of crisis services (across 36 reports), 42 research studies (across 48 reports) and 54 grey literature documents. The organisation of crisis services has been categorised as follows: triage/assessment only, digitally mediated support approaches, and intervention approaches and models. When looking at experiences of crisis care, the following four themes were identified: (1) barriers to and facilitators of seeking and accessing appropriate support; (2) what children and young people want from crisis services; (3) children's, young people's and families' experiences of crisis services; and (4) service provision. In determining effectiveness, the findings are summarised by type of service and were generated from single heterogenous studies. The goals of a crisis service should be to (1) keep children and young people in their home environment as an alternative to admission; (2) assess need and plan; (3) improve children's and young people's and/or their families' engagement with community treatment; (4) link children and young people and/or their families to additional mental health services, as necessary; (5) provide peer support; (6) stabilise and manage the present crisis over the immediate period; and (7) train and/or supervise staff. The key limitation of this review was that much of the literature was drawn from the USA. Owing to the differences between USA and UK in terms of commissioning and delivering services, approaches to crisis care operating in the USA may not be directly applicable to the UK. Future work As only three research studies included in this evidence synthesis had been completed in the UK, a clear case exists for the commissioning of new high-quality studies to generate knowledge about the efficacy and acceptability of crisis care approaches operating in the UK. Future empirical research in this area is planned. Study registration: This study is registered as PROSPERO CRD42019160134. Funding This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 11, No. 3. See the NIHR Journals Library website for further project information. Plain language summary We wanted to know more about services for children and young people in mental health crisis. The aim was to investigate what research on this topic has already been completed, and we were specifically interested in what people think of crisis care, the goals of crisis services and whether or not crisis care is helpful. In our evidence synthesis, we included research and other documents (e.g. policies). We used a systematic approach to find relevant research from January 1995 to January 2021 and worked with a Stakeholder Advisory Group (comprising people able to provide expertise through personal experience, practitioners and other researchers) whose members helped us locate relevant published material. The Stakeholder Advisory Group also helped us find important reports and websites. We used a clear process to decide whether or not to include each research paper found, reflecting the aim of our study, and whether or not the research had been completed to a good-enough standard. We included 48 primary research articles, 36 descriptive accounts of different crisis services and 54 other types of documents. We categorised crisis services as being organised in the following ways: triage/assessment only, digitally mediated support approaches, and intervention approaches and models. When looking at experiences of crisis care, we found literature on the following topics: barriers to and facilitators of seeking and accessing appropriate support; what children and young people want from crisis services; children's, young people's and families' experiences of crisis services; and service provision. As the included studies were different in nature, we were unable to clearly determine what models of crisis care work. We found seven clear goals of crisis intervention, that is, crisis services (1) assess and plan care, (2) stabilise and manage the current crisis period, (3) keep children and young people in their home environment, (4) help children and young people and their families to engage with community treatment, (5) help children and young people and their families access additional mental health services, (6) help with access to peer support and (7) train and supervise other staff. Scientific summary Background The mental health of children and young people (CYP) is a rising concern, with one in six children aged 5-19 years in England having a probable diagnosable mental disorder. A recent National Assembly inquiry found a 100% increase in demand for CYP mental health services in Wales between 2010 and 2014. With resources stretched, and CYP often waiting lengthy periods to be seen, increasing numbers of CYP are seeking help at a point of crisis. During periods of crisis, it is vital that care is timely, effective and based on evidence. Crisis care for CYP has become a national and international policy priority, with substantial funding allocated to the development of crisis services. The needs of young people in crisis can be met through clinical services, such as local child and adolescent mental health (CAMH) teams, crisis teams, and accident and emergency departments, or through school counselling, youth services and internet-based counselling. In the UK, the landscape of crisis care delivery has shifted substantially in recent years. Notably, investments have been made in community crisis teams that aim to provide care close to home and avoid the need for hospital admission. Different forms of crisis support from health, education, social care and the third sector are available for CYP, with considerable regional variability in the way such care is delivered. However, little is known about how these different services are organised or experienced, whether or not they are effective, or how they are integrated within their local system contexts. Objectives The review objectives of this study were to critically appraise, synthesise and present the best-available international evidence relating to crisis services for CYP aged 5-25 years. Specifically, we look at: the organisation of crisis services across education, health, social care and the third sector the experiences and perceptions of CYP, families and staff to determine the effectiveness of current models to determine the goals of crisis intervention. Methods The protocol was crafted following the guidance published by the Centre for Reviews and Dissemination at the University of York (York, UK).